The Influence of Transformational Leadership, Organizational Culture, Reward and Commitment to Lecture Performance In The Central Java Region - Maylane Boni Abdillah; Tri Joko Rahardjo; Martono Martono; Titi Prihatin (Universitas Negeri Semarang, 2021)
Lecturer performance was an important factor in an effort to ensure the quality management of higher education institutions. Because the performance of lecturers is a measure of the abilities and skills of personnel in carrying out their duties and responsibilities. The purpose of this study was to analyze the influence of transformational leadership, organizational culture, appreciation of commitment to integrated goals, to analyze the influence of transformational leadership, organizational culture, rewards, and commitment to lecturer performance. Methods: this research Was a quantitative research with a research step (design) a structural equation model (Structural Equation Model) through a Second Order Confirmatory Factor Analysis model approach. The object of research was a private university lecturer in the coordination scope of LL Dikti Region VI Central Java who has a minimum functional position of Expert Assistant. This research was conducted from November to December 2020. The research sample was 365 lecturers of the Krejcie and Morgan formulas and purposive sampling technique. Research variables consist of transformational leadership, organizational culture, rewards, commitment to integrated goals and lecturer's research performance, with 20 indicators.